1990
DOI: 10.1111/j.1440-1746.1990.tb01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of hepatitis B core antigen in the liver in patients with chronic hepatitis B and its relation to hepatitis B virus DNA

Abstract: Liver biopsies from 52 patients with chronic hepatitis B were investigated for the presence and distribution of HBcAg and the results were compared with the status of hepatitis B virus deoxyribonucleic acid (HBV-DNA). The patients consisted of 37 men and 15 women, aged 16-55 years (mean = 34 years). Serum alanine aminotransferase (ALT) was elevated in 50 patients (range: 18-969 U/L; mean = 290 U/L). Serological testing showed HBsAg in all, HBeAg in 45 (87%), and HBV-DNA in 28 (54%). Liver biopsies demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Clinically, hepatic HBc in patients with minor hepatitis activity was distributed mainly in the nuclei. In contrast, in patients with chronic active liver diseases, hepatic HBc was distributed predominantly in the cytoplasm [14], [15], [16], [17], [18]. Mature cytoplasmic core particles contain relaxed circle (RC) DNA genome, which needs to be transported to nucleus for conversion into covalently closed circular DNA [7], [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, hepatic HBc in patients with minor hepatitis activity was distributed mainly in the nuclei. In contrast, in patients with chronic active liver diseases, hepatic HBc was distributed predominantly in the cytoplasm [14], [15], [16], [17], [18]. Mature cytoplasmic core particles contain relaxed circle (RC) DNA genome, which needs to be transported to nucleus for conversion into covalently closed circular DNA [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies on this issue were performed in the context of HBc expression without HBV viral replication [23], [24], [25]. It is known that more predominant cytoplasmic HBc tends to be associated with more active HBV DNA replication [14], [15], [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…As these bodies form early in infection from the core protein subunits, the mechanism of nuclear entry of the hepadnavirus core protein is probably different from the intensively studied nuclear targeting of mature HBV nucleocapsids (Kann et al, 1999;Pante & Kann, 2002;Rabe et al, 2003). Additionally, in low-level-producing cells such as those present in chronically infected patients or HBVtransgenic mice, the core protein accumulates preferentially in the cell nucleus (Chu et al, 1995;Gowans et al, 1985;Larkin et al, 1999;Naoumov et al, 1990;Serinoz et al, 2003;Yoo et al, 1990), predominantly as empty capsids (Farza et al, 1988; Guidotti et al, 1994). This masks a possible specific localization of HBc subunits.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports concerning the distribution of HBV-related proteins and HBV-DNA observed directly using immunohistochemistry and in situ hybridization [Burrell et al, 1984;Pontisso et al, 1985;Kiyosawa et al, 1988;Yoo et al, 1990;Chu and Liaw, 1992;Naumov et al, 1993;Wu et al, 1996;Lindh et al, 1999;Rodriguez-Inigo et al, 2003;Karpinska et al, 2004;Mariscal et al, 2004]. Some studies have shown, that HBV replicates diffusely in the hepatic lobules in the early phase of chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%